Virtual Engine In-Cylinder Pressure Sensor for Automobiles and Agricultural Tractors. (2020) - Han, Runzhe; Bohn, Christian; Bauer, Georg
Abstract: The cylinder pressure signal is a very useful indicator for advanced high-performance internal-combustion engines equipped in modern automobiles and agricultural tractors. In this paper, a previous framework for the cylinder pressure estimation is conducted based on a transfer path model (between the cylinder pressure signal and the vibration signal) identified in frequency domain. The main idea behind the previous framework is based on the Kalman filter (of which the input is the engine structure vibration) for the augmented model formed by augmenting the cylinder pressure signal model with delay blocks and the transfer path model identified in time domain. Two combustion metrics, pressure peak P max and peak location P loc, are used for evaluating the estimation framework under the transfer path identified in frequency domain. The estimation results are compared with both experimental data collected from a four-cylinder diesel engine and previous work results, and illustrate the effectiveness of the newly identified transfer path.